Sustainable agricultural production systems - Martínez-Castillo, Róger (2016)
Sustainable development is based on ethical principles such as respect for and harmony with nature, political values such as participative democracy and social equity, and moral norms such as environmental rationality. Sustainable development is egalitarian, neutral, and self-managed, able to satisfy the basic needs of people, respecting cultural diversity, and improving the quality of life. The concepts of agriculture and sustainable development refer to the need of minimizing degradation of fertile land, while working to increase production. They include agricultural activities such as soil and water management, crop management, and the conservation of biodiversity, taking into account the provision of food and raw materials. Sustainability of agricultural production systems refers to the capacity of the system to maintain its productivity in spite of economic and natural, external or internal limitations. Sustainability is a function of the natural features of a system and the pressures and interventions it experiences, as well as social, economic, and technical interventions that are carried out in order to fight negative pressures, highlighting the resiliency of the system.